PHYSICAL WORKOUT APPLICATION FOR BASKETBALL PLAYERS - Suwarno Suwarno; Derrick Derrick (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Physical fitness is one of the important factors for a basketball player. Because basketball is a sport that has a lot of physical contact with other players. Therefore, basketball athletes are required to have a good level of physical fitness. In this study, we will research the physical workout application for basketball players where this application is made using the Software Development Life Cycle (SDLC) Waterfall method and backtracking algorithm. This research method consists of 5 stages, such as requirements analysis stage where we collect materials that need to be used, designing stage where the project will be designed, Implementation stage where the project will be developed, testing stage where the project will be tested, and deployment stage where the project will be distributed. Due to this pandemic condition, several countries have limited their activities outside the house because of that many people do most of their activities inside their house. This results in them not being able to go to the gym or other places to work out. So, with this research, they can do workout without having to leave the house.